PERBANDINGAN EFEKTIFITAS KOMPRES HANGAT DAN KOMPRES DINGIN UNTUK MENGURANGI INTENSITAS NYERI PASCA OPERASIPADA PASIEN FRAKTUR - Yuwiguna, Fanni Satria; ", Bayhakki "; Sabrian, Febriana " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This study aimed to compare the effectiveness of cold compresses and warm compresses to reduce the intensity of postoperative pain in patients with fractures. The design of this research used type of research in this study is quasy experiment with pretest and posttest design with two comparison treatments. The sample are divided into which warm compresses (15 patients) and cold compresses group (15 patients) taken by purposive sampling with inclusion criteria. The instrument tool that applied for both of group was observation form such as Numeric Rating Scale (NRS).Cold and warm compresses were given for 5-10 minutes in each group. The data was analysed using univariate and bivariate with mann-whitney. The results showed that the average intensity of pain in the group before being given a warm compress by 3.07 and 2.00 after. Furthermore, the average pain intensity on a cold compress is a group of 3.47 before and 1.87 after a cold compress. The mann-whitney test results showed that p value = 0.00 <0.05, it means that there are significant differences in pain intensity between before and after the cold compress. This shows that the administration of an effective cold compress more effective in reducing pain intensity in patients with fractures. Keywords: fracture, pain intensity, cold compresses